Pollination ecology of Steveniella satyrioides (Spreng.) Schltr. (Orchidaceae) in Ayan natural landmark (the Crimea) - Fateryga, A.V.; Ivanov, S.P.; Fateryga, V.V. (Український ботанічний журнал, 2013)
The nectarless orchid, Steveniella satyrioides (Spreng.)
Schltr., occurs in the mountain part of the Crimean Peninsula; it is known from 26 localities 10 of which were found during the last 50 years. Pollination ecology of the species was
studied in Ayan Natural Landmark (Simferopol District). From
1 to 55 individuals of this species flowered here in different
years; one year there was no flowering plants. The pollination
rate of S. satyrioides varies from 16 % to 79 % and positively
correlates with the density of specialized pollinators — females
of diplopterous wasps of genera Vespula Thomson, 1869, and
Dolichovespula Rohwer, 1916. A probable mechanism of attraction of wasps by flowers of S. satyrioides and its evolution
are discussed. Безнектарна орхідея Steveniella satyrioides (Spreng.) Schltr. поширена в Криму в межах гірської частини півострова та відома з 26 локалітетів, 10 з яких представлено знахідками, зробленими в останні 50 років. Вивчено екологію запилення виду в урочищі Аян (Сімферопольський р-н). У різні роки тут цвіло від 1 до 55 екземплярів даного виду, в один із років — жоден. Рівень запилення S. satyrioides коливається від 16 до 79 % і по- зитивно корелює зі щільністю спеціалізованих запилювачів — самок складчастокрилих ос родів Vespula Thomson, 1869 і Dolichovespula Rohwer, 1916. Обговорюється можливий механізм залучення ос на квітки та його еволюційне становлення. Безнектарная орхидея Steveniella satyrioides (Spreng.) Schltr. распространена в Крыму в пределах горной части полуострова и известна из 26 локалитетов, 10 из которых представлены находками, сделанными в последние 50 лет. Изучена экология опыления вида в урочище Аян (Симферопольский р-н). В разные годы здесь цвело от 1 до 55 экземпляров данного вида, в один год — ни один. Уровень опыления S. satyrioides колеблется от 16 до 79 % и положительно коррелирует с плотностью специализированных опылителей — самок складчатокрылых ос родов Vespula Thomson, 1869 и Dolichovespula Roh wer, 1916. Обсуждается возможный механизм привлечения ос на цветки и его эволюционное становление.